2017
DOI: 10.1177/0886260517742911
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events Exposure and Psychological Trauma in Children Victims of War in the Gaza Strip

Abstract: The present article studies war-related trauma and its effects on children living in the Gaza Strip, 6 months after the attack launched by the Israeli army on July 8, 2014, which lasted for 51 days. The objective was twofold: (a) to identify the prevalence of exposure to traumatic events and (b) to examine the symptoms of traumatic stress in children as described by their parents or tutors using the Harvard Trauma Questionnaire (HTQ). Data from 1,850 male and female children aged between 6 and 15 years living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
0
22
0
6
Order By: Relevance
“…Research e reveals the frequent violence and torture that migrants/refugees suffer by police and border agents in their attempt to reach the European Union (Arsenijevic et al, 2017;Crepet et al, 2017;Farhat et al, 2018;Koning, 2019). Psychologically, exposure to these violent episodes during transit serves to add to previous traumatic events and increases the risk of mental health issues for migrants and refugees (Dimitry, 2012;Manzanero et al, 2017).…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…Research e reveals the frequent violence and torture that migrants/refugees suffer by police and border agents in their attempt to reach the European Union (Arsenijevic et al, 2017;Crepet et al, 2017;Farhat et al, 2018;Koning, 2019). Psychologically, exposure to these violent episodes during transit serves to add to previous traumatic events and increases the risk of mental health issues for migrants and refugees (Dimitry, 2012;Manzanero et al, 2017).…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…As an example of the population's potential exposure to traumatic events, the 2014 war lasted 54 days and carried a reported death toll of 2,251, including 299 women and 551 children; 11,231 individuals were wounded, including 3,540 women and 3,436 children; 18,000 housing units were destroyed; and about 500,000 people were displaced [5]. Studies have documented that Gazan children have experienced displacement and/or witnessed death, shelling, and combat situations [6]. Studies have further indicated that 64 to 67% of children in Gaza demonstrate clinical levels of posttraumatic stress symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The main cause is the sample analyzed. Sometimes they are clinical samples, therefore they are already skewed from the start, as they do not contemplate in the study the non-clinical population that would be the majority among adult (Steel et al, 2009) and children (Dimitry, 2012;Manzanero et al, 2017) victims. On the other hand, the memories studied are difficult to contrast from the point of view of their reality, for example, in child sexual abuse.…”
Section: Problems In Studying Traumatic Memoriesmentioning
confidence: 99%